PENGARUH ASAM ASKORBAT ORAL TERHADAP KERUSAKAN SEL ENDOTEL KORNEA PADA FAKOEMULSIFIKASI - , dr. Nika Bellarinatasari, dr. Tri Wahyu Widayanti, SpM, KVR, MKes ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Phacoemulsification cataract surgery is ABSTRACT the most popular of cataract surgery technique that can damage corneal endothelial cell. Ascorbic acid can reduce corneal endothelial cell damage. The objective of this study was to compare the corneal endothelial cell loss due to phacoemulsification surgery in ascorbic acid group and placebo group This was a clinical study with double blinds randomized controlled trial. There were 66 subjects enrolled, divided into 2 groups, ascorbic acid group that was given 2 g orally with divided doses 500 mg four times at night, morning, afternoon and 2 hours before surgery (n=32) and placebo group (n=34). Endothelial cell counts were performed before and 7 days after phacoemulsification surgery. Administration of 2 g ascorbic acid in divided doses of 500 mg given 4 times before phacoemulsification surgery caused less corneal endothelial cell loss 229,27 ± 191,58 cells/mm 2 (9,10% ± 6,88%) compared with the administration of placebo had endothelial cell loss 364,64 ± 255,25 cells/mm 2 (14,85% ± 10,54%). There are statistically significantly different in endothelial cell loss between the two groups (p<0,05), but no clinically significantly different. The baseline characteristic between the both groups was similar. 2 g In conclusion, administration of ascorbic acid in divided doses of 500 mg given 4 times before phacoemulsification surgery can reduce the corneal endothelial cell loss